The Reward and Punishment of the Civil Servants Apparatus In the Civil Service Police Unit and Wilayatul Hisbah Bener Meriah Regency - Fadhlon Saputra; Muhammad Bin Abubakar; M. Akmal (Master Program of Sociology, Universitas Malikussaleh,, 2020)
This study examines the provision of rewards and punishments to ASN. The research objective was to understand how the process and impact of reward and punishment for ASN in Satpol PP and WH Bener Meriah Regency. The theoretical perspective used is the theory of public organizations, reward, and punishment, and the state civil apparatus. The research method used is qualitative. The results showed that the process of giving rewards and punishments was carried out in three stages: ASN inventory, priority scale creation, and decision making. The positive impact of giving rewards and punishments for ASNs in the Satpol PP and WH Office of Bener Meriah Regency is to increase work motivation and can help develop careers for ASNs. Whereas punishment has a positive impact on ASNs as a deterrent effect from repeating violations of duty and can improve their behavior at work which is then able to improve their performance in the future. The negative impact did not change the attitude/behavior of ASNs who were given punishment because they were annoyed at getting punished, or it could be said that ASN was not deterred by the actions of giving punishment by the leaders of Satpol PP and WH in Bener Meriah Regency.